2021
DOI: 10.1002/nag.3193
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional lattice Boltzmann simulation of the permeability of soil‐rock mixtures and comparison with other prediction models

Abstract: With the discrete element method and the proposed virtual slicing technique for three‐dimensional discrete element model, random pore‐structural models of soil‐rock mixtures (SRMs) are constructed and voxelized. Then, the three‐dimensional lattice Boltzmann method (LBM) is introduced to simulate the seepage flow in SRMs on the pore scale and the influences of rock content, rock size, relative density on the simulated permeability of SRMs are comprehensively investigated. Finally, several theoretical models are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The reason is that the SRM used in the experiment has soil and rock particles that are mostly attached, whereas the SRM made by the mathematical model has sandy particles that do not have a bond, so the permeability is larger. Compared with the reenactment computation effects of SRM's penetrability described in Reference [34], it is consistent with the calculation data reported in this paper.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The reason is that the SRM used in the experiment has soil and rock particles that are mostly attached, whereas the SRM made by the mathematical model has sandy particles that do not have a bond, so the permeability is larger. Compared with the reenactment computation effects of SRM's penetrability described in Reference [34], it is consistent with the calculation data reported in this paper.…”
Section: Discussionsupporting
confidence: 91%
“…The influence of particle size on permeability was clearly linked to rock content in the conclusion of Reference [35]. Compared with Reference [34], this study found that the soil/rock particle size feature ratio extent similarly has a particular threshold, which can cause an unforeseen increase in simulated permeability, and the two had explicit similarities in this regard.…”
Section: Soil/rock Particle Size Feature Ratio Pmentioning
confidence: 45%
See 2 more Smart Citations